Removal of Dyes Using Pamam Dendrimer: A Review And Bibliometric Analysis - Kanak Saxena (Indonesian Journal of Limnology, 2023)
Pollution caused by increasing industrial activities, particularly dye pollution in water bodies, has posed significant challenges for researchers. As a result, researchers have continued to prioritize the elimination of dyes, motivated by the necessity to protect water quality and reduce the accompanying hazards. Addressing this issue has prompted various approaches, with adsorbents emerging as a promising solution. Among these adsorbents, Poly(amidoamine) (PAMAM) has shown substantial potential in the field of dye removal. This article undertook a review of published articles in this relevant domain and conducted a bibliometric analysis. A total of 36 articles were identified up to the year 2022 and various PAMAM derivatives and the dyes they removed were cataloged. The comparative analysis encompassed articles, authors, journals and countries, highlighting the importance of the research in this area. Furthermore, the article established relationships through co-citation analysis, shedding light on the interconnectedness of research in the field. To visually represent the data, VOSviewer software was employed to create maps, making the findings more accessible and comprehensible.